Analysis of the Myth on Western Aid to Lithuanian Partisans - Arlauskaitė-Zakšauskienė , Inga (Genocidas ir rezistencija, 2014)
There were many factors which affected the emergence of the statement on “western aid”: the Soviet propaganda, communist terror, Lithuanian partisans, Western radio stations, Western intelligence services and others. In order to understand how the hope to receive help from the West spread among partisans, the geopolitical and historical space of the time must be assessed from several perspectives – starting from the dynamics of international relations after WWII finishing with the mentality of freedom fighters and the factors that shaped the outlook of partisans as individuals.In the 1940s, five western radio stations could be received in the territory of Soviet Lithuania: Vatican Radio, BBC, Voice of America, Radio Free Europe and Radio Liberty. The British radio station BBC never had a Lithuanian language service and did not broadcast in Lithuanian, but partisans could listen to broadcasts in the Russian language. As testified by the partisan underground press and memoirs, the BBC was one of the main sources of objective information from the West. As the BBC had strict rules for its programmes, this broadcaster could not contribute to the dissemination of the myth regarding Western aid to the occupied countries.On 16 February 1951, the US Voice of America started broadcasting in the Lithuanian language. Due to its association with the Department of State Security, this radio station was treated by the Soviet Union as a tool of official US policy. Because of its late start in broadcasting in the Lithuanian language and dependence on the dynamics of the US–USSR relationship, the Voice of America could not have initiated the idea of Western aid to the partisans. The Soviet Union was most critical of the US radio stations Radio Liberty and Radio Free Europe, which started broadcasts in the Lithuanian language only in the early seventies, when the resistance struggle was long over and the strict radio rules and censorship did not allow these radio stations to contribute to the dissemination of the myth on Western aid.The belief of partisans that Lithuania would be freed, based on international documents (Freedom Charter) and the well-known geopolitical situation, could have determined the hope that soon the countries of the East and the West would be at war. The development of the Western aid myth, therefore, was formed by the model of historical consciousness of freedom fighters and the culture of historical memory. After WWII, people in Lithuania not only remembered the interwar period of Lithuanian independence, but many also participated in the armed defence of the state of Lithuania in 1918–1919. Participants of the independence struggle still remembered their own help to the re-established state, German volunteers, American legion of volunteers, and the 1941 June Uprising, which succeeded due to the outbreak of WWII. The memory of recent events was favourable for the emergence of the said beliefs of Lithuanian partisans. Historical images and ideas preserved in the memories of the people of that time influenced the collective consciousness and helped partisans to remain persuaded and contributed to their hope that in the event of war between former allies, Western countries would liberate Lithuania.
Keywords: soviet occupation; armed resistance; USA; propaganda; partisans